(untitled) (Progressive Agriculture, 2018)
Fisheries sector has high potential for the economic development of Bangladesh. Bangladesh earns a considerable amount of foreign currencies by exporting fish, shrimps and other fisheries products. This study addresses profitability of tilapia production using benefit cost ratio. The study also examines input demand and output supply of tilapia farming in Bangladesh by applying a profit function approach. Results revealed that benefit cost ratio is greater than 1, means that tilapia production is profitable in the study area. Tilapia farmers are also responsive to changes in market prices of inputs and outputs. Tilapia price is the most dominant determinant of output supply and input demand. A 1% increase in tilapia price will increase output supply by 3.836% and increase demand for lime, fingerlings, feed and labour by 0.941%, 0.987%, 0.523% and 1.00%, respectively. Problem facing index analysis shows major problems faced by the farmers were low market price of tilapia, high prices of fish feed with adulteration and inadequate supply of good quality fry. Progressive Agriculture 29 (3): 248-258, 2018